Embryo Density and Its Neutrality in Day-3 Embryo Development: A Retrospective Cohort Study - Cheng Shi; Tie Cheng Sun; Shi Hui Meng; Ping Wang; Rong Liang; Sheng Nan Duan; Hong Jing Han; Ya Nan Liu; Huan Shen; Xi Chen (International Journal of Endocrinology)
Introduction. Many studies have shown that embryo density has an impact on day-3 embryo-developmental outcomes; however, embryo density remains controversial in clinical practice. We aimed to evaluate the association between embryo density and day-3 embryo-developmental outcomes in real world with the largest sample size. Methods. In 2018, we identified 10941 day-3 embryos from all female patients (n = 1568) in the study. The embryos were allocated to three embryonic densities: 30 μl/embryo (individual culture), 15 μl/embryo, and 10 μl/embryo (group culture). The primary outcomes were cleaving speed, quality, and proportion of successful implantations. The generalized estimate equation (GEE) model was used both in the univariate analysis and multivariable logistic regression analyses to investigate the relationship between embryo density and embryo-developmental outcomes. Results. There were 3064, 5695, and 2182 embryos in the 30 μl/embryo group, 15 μl/embryo group, and 10 μl/embryo group, respectively. The proportions of 7–10 cell embryos were 57.2%, 56.1%, and 58.3% in three densities with no statistical significance (P=0.37), respectively. The proportions of morphologically good embryos were 20%, 20.3%, and 20% in three densities with no statistical significance (P=0.85), respectively. Proportions of implanted embryos were 37.7%, 37.1%, and 27.8% with no statistical significance (P=0.36), respectively. After adjustment for confounders, which were significant in the univariate analysis, the embryo density was still not associated with day-3 embryo-cleaving speed, day-3 embryo quality, and day-3 embryo-implanting potential (all P>0.05). Conclusion. In a 30 μl microdrop, the culturing embryos with embryo densities of 15, 10, and 30 μl/embryo (from zygotes to day 3) had similar developmental outcomes. The embryo density had no impact on day-3 embryo development.